Magnetic Sensors : Principles and Applications - Kuang, Kevin; Kuang, Kevin (IntechOpen, 2012)
This book provides an introductory overview of the research done in recent years in the area of magnetic sensors. The topics presented in this book range from fundamental theories and properties of magnets and their sensing applications in areas such as biomedicine, microelectromechanical systems, nano-satellites and pedestrian tracking. Written for the readers who wished to obtain a basic understanding of the research area as well as to explore other potential areas of applications for magnetic sensors, this book presents exciting developments in the field in a highly readable manner.
English
Keywords: Circuits & components; Electronic devices & materials